Activation of nucleus accumbens NMDA receptors differentially affects appetitive or aversive taste learning and memory - Nuñez-Jaramillo, Luis; Rangel-Hernández, José A.; Burgueño, Belén; Miranda, Maria-Isabel (Frontiers in Behavioral Neuroscience, 2012)
Taste memory depends on motivational and post-ingestional consequences; thus, it can be aversive (e.g., conditioned taste aversion, CTA) if a novel, palatable taste is paired with visceral malaise, or it can be appetitive if no intoxication appears after novel taste consumption, and a taste preference is developed. The nucleus accumbens (NAc) plays a role in hedonic reactivity to taste stimuli, and recent findings suggest that reward and aversion are differentially encoded by the activity of NAc neurons. The present study examined whether the requirement for NMDA receptors in the NAc core during rewarding appetitive taste learning differs from that during aversive taste conditioning, as well as during retrieval of appetitive versus aversive taste memory, using the taste preference or CTA model, respectively. Bilateral infusions of NMDA (1 μg/μl, 0.5 μl) into the NAc core were performed before acquisition or before retrieval of taste preference or CTA. Activation of NMDA receptors before taste preference training or CTA acquisition did not alter memory formation. Furthermore, NMDA injections before aversive taste retrieval had no effect on taste memory; however, 24 h later, CTA extinction was significantly delayed. Also, NMDA injections, made before familiar appetitive memory retrieval, interrupted the development of taste preference and produced a preference delay 24 h later. These results suggest that memory formation for a novel taste produces neurochemical changes in the NAc core that have differential requirements for NMDA receptors during retrieval of appetitive or aversive memory.